1997
DOI: 10.1159/000189535
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Renal Nuclear Oxalate Binding Activity in Experimental Hyperoxaluric Rats

Abstract: The hyperoxaluric rat kidney nucleus exhibited a 50% increase in oxalate binding activity of control in both the residual fraction containing nuclear envelopes and the histone fraction with a concomitant increase in basal lipid peroxidation and a decrease in thiol content. However, in vitro lipid peroxidation induced by the ascorbate-ADP-Fe3+ system increased the oxalate binding activity of the residual fraction with a positive correlation but inhibited the histone oxalate binding activity with a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Earlier studies have shown the presence of oxalate-binding proteins in rat and human renal inner mitochondrial membranes [22]and histone H 1 B [23]and their excessive activities in hyperoxaluria. Further, these proteins have been shown to have an enhanced oxalate-binding activity in hyperoxaluric state or when subjected to lipid peroxidation [24, 25]. Based upon the above findings, we have studied the role of the 23-kD COM crystal adsorbed protein to resolve some aspects in the etiology of calcium oxalate stone pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown the presence of oxalate-binding proteins in rat and human renal inner mitochondrial membranes [22]and histone H 1 B [23]and their excessive activities in hyperoxaluria. Further, these proteins have been shown to have an enhanced oxalate-binding activity in hyperoxaluric state or when subjected to lipid peroxidation [24, 25]. Based upon the above findings, we have studied the role of the 23-kD COM crystal adsorbed protein to resolve some aspects in the etiology of calcium oxalate stone pathogenesis.…”
Section: Discussionmentioning
confidence: 99%